2015
DOI: 10.1097/hnp.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Diabetes in the Elderly and Affecting Factors

Abstract: This study was conducted with the goal of evaluating the challenge of diabetes in elderly individuals and affecting factors. This descriptive study was conducted with 88 diabetic patients 65 years of age or older who were admitted to the endocrinology and metabolism disorders outpatient clinic data of the study collected by using a questionnaire prepared by the researchers and the Elderly Diabetes Burden Scale. Total score of the scale varies between 19 and 92 points. While a higher score indicates a higher bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
11
3
1
Order By: Relevance
“…This measure, Willingness to Accept Life-Sustaining Treatment (WALT) was also utilized by Janssen et al [ 44 ] for Dutch patients with two of the three conditions explored by Fried et al [ 80 ]: chronic obstructive pulmonary disease and chronic heart failure. Other authors stated that they measured treatment burden but provided minimal or no detail on the actual measurement process or sub-scales used [ 20 , 44 , 48 , 55 , 56 , 78 ]. Readers would therefore need to search beyond the paper to identify what dimensions of treatment burden were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This measure, Willingness to Accept Life-Sustaining Treatment (WALT) was also utilized by Janssen et al [ 44 ] for Dutch patients with two of the three conditions explored by Fried et al [ 80 ]: chronic obstructive pulmonary disease and chronic heart failure. Other authors stated that they measured treatment burden but provided minimal or no detail on the actual measurement process or sub-scales used [ 20 , 44 , 48 , 55 , 56 , 78 ]. Readers would therefore need to search beyond the paper to identify what dimensions of treatment burden were included.…”
Section: Resultsmentioning
confidence: 99%
“…from carrying, storing, and administering medication, and impact on lifestyle, e.g. diabetic medication and effect on meal times, exercise and/or diet [ 19 , 48 , 79 ]. Alternatively, one broad treatment burden question was included by Hanke et al [ 43 ], who asked participants with actinic keratosis how much of a problem had the treatment been, ‘for example by making your home messy, or by taking up time?’ Some studies identified the total number of therapeutic drug classes or medications a person was taking, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus is a chronic disease with a multifactorial pathogenesis and etiology that are related to the complex interactions between genetic and environmental factors. Increased life expectancy, a sedentary lifestyle and a poor diet have also contributed to the higher rates of type 2 diabetes mellitus worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Hastaların düzenli rehabilitasyon programına dâhil edilmesi hastane başvurularını azaltacağı gibi, gerekli olmayan ilaç tüketimini de önleyerek ekonomik kaybı azaltacaktır. 4 Günlük yaşam aktivitelerinin ele alındığı bir çalışmada, kronik obstrüktif akciğer hastalığı (KOAH) ve kalp yetersizliği olan hastaların bakımda en fazla bağımlı oldukları günlük aktivite alanlarının; hareket, giyinme, vücut temizliği, boşaltım ve tehlikelerden kaçınma olduğu saptanmıştır. 5 İnsanın fizyolojik olarak hayatını sürdürebilmesi için temel gereksinimlerinin karşılanması zorunludur.…”
unclassified